"As Good as a Boy" But Still a Girl: Gender Equity Within the Context of China's One-Child Policy. (March 2022) - Wang, Yijie; Zhang, Yanan
What would happen if gender inequality were suddenly and forcefully proclaimed to be non-existent by the authorities? The Chinese one-child policy has to some extent functioned as a unique social experiment to answer this question. Historically, sons have been preferred in China. Yet, with the restriction of one child per family, many people have been rendered sonless and forced to find solace in the well-known propaganda slogan: "Having a girl is as good as having a boy." Delving into the life experiences of singleton daughters in urban China, this study reveals that, within nuclear families, daughters are in many ways treated as if they were sons, which demonstrates people's potential to overcome previous gender discrimination when circumstances require. However, outside the realm of nuclear families, the treatment of daughters as akin to sons falters, dissolves, or backfires in various ways, revealing that true equality cannot be achieved without a radical confrontation and systematic adjustment of existing power relations. This study contributes to understanding gender equality in China while also serving to document lived experiences in relation to a unique policy that was recently abolished.